Clinical analysis of lupus miliaris disseminatus faciei: a cross-sectional study and literature review - Wang, Yaqi; Li, Jiahui; Wang, Shuang (Frontiers in Medicine, 2024)
The clinical similarity of lupus miliaris disseminatus faciei (LMDF) and other papular granulomatous facial disorders often makes its correct diagnosis challenging. Diagnosis often requires the assistance of pathological examination, and dermoscopy can be used as an auxiliary and non-invasive examination method, however, the current findings remain incomplete. Objectives: This study aimed to summarize the clinical, histopathological and dermoscopic features of LMDF in the Chinese Han population and aiming to provide practical significance to correct diagnosis.. Methods: 109 patients of LMDF were collected in the Department of Dermatology, the Second Affiliated Hospital of Xi'an Jiaotong University from August 2015 to August 2023. Clinical and histopathological manifestation, as well as 44 cases of dermoscopic image features, including background, follicular findings, vessels, and other structures, were summarized and evaluated. The clinical and histopathological manifestations of all patients, as well as the dermoscopic image features of 44 cases, including background, follicular findings, vessels, and other structures, were summarized and evaluated.The most significant histopathological features of LMDF in 109 cases is epithelioid granulomatous infiltrate in the superficial dermis, with or without caseation.The most significant dermoscopic features of LMDF in all 44 cases were orange structureless background (30/44), follicular plug (32/44), follicular white scar-like area (32/44), unspecific linear vessels (24/44), linear vessels with branch (24/44) and white streaks (18/44).Conclusions: Histopathologically, LMDF is characterized by the presence of epithelioid granulomatous infiltrate in the superficial dermis, with or without caseation.Dermoscopically, it exhibits a distinctive orange structureless background, follicular plug, follicular white scar-like area, nonspecific linear vessels, linear vessels with branches, and white streaks.